2022
DOI: 10.1158/2326-6066.cir-21-0643
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine-Deaminase-Acting-on-RNA-1 Facilitates T-cell Migration toward Human Melanoma Cells

Abstract: The effect of tumor/T-cell interactions on subsequent immune infiltration is undefined. Here we report that pre-exposure of melanoma cells to cognate T cells enhanced the chemotaxis of new T cells in vitro. The effect was HLA class I–restricted and IFNγ-dependent, as it was abolished by β2M-knockdown, MHC-blocking antibodies, JAK1 inhibitors, JAK1-silencing and IFNgR1-blocking antibodies. RNA-sequencing of 73 melanoma metastases showed a significant correlation between the interferon-inducible p150 isoform of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…One study showed that the deletion of PTPN2 phosphatase in T cells promotes antitumor immunity and CAR T-cell efficacy in solid tumors [ 33 ]. Another study demonstrated that ADAR promotes T-cell migration to human melanoma cells [ 34 ]. In addition, ADAR has been shown to improve Treg cell function via the miR-21b/Foxp3 axis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that the deletion of PTPN2 phosphatase in T cells promotes antitumor immunity and CAR T-cell efficacy in solid tumors [ 33 ]. Another study demonstrated that ADAR promotes T-cell migration to human melanoma cells [ 34 ]. In addition, ADAR has been shown to improve Treg cell function via the miR-21b/Foxp3 axis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This positive feedback mechanism could have crucial effects on the growth of hot tumors as well as the great response to immunotherapy. 281 Antienzyme inhibitor 1(AZIN1) is one of the most prevalent Ato-I RNA-edited proteins in several human cancers. The functional effects of RNA-edited AZIN1 on tumor angiogenesis have been exhaustively studied recently.…”
Section: -Methylcytosinementioning
confidence: 99%
“…This positive feedback mechanism could have crucial effects on the growth of hot tumors as well as the great response to immunotherapy. 281 …”
Section: Introductionmentioning
confidence: 99%
“…ADAR1 has two subtypes of promoters, that is, the p110 and p150 subtypes, which have different roles in cancer development [ 4 ]. In melanoma, silencing the ADAR1-p150 subtype abolishes IFN-γ-driven T-cell migration, and silencing and overexpressing the ADAR1-p110 subtype reduces and increases T-cell migration, respectively [ 5 ]. ADAR1 regulates the peritoneal implantation and metastasis of gastric cancer cells through Wnt/β-catenin signaling in gastric cancer tissue [ 6 ].…”
Section: Introductionmentioning
confidence: 99%